Summer Grazing of Steers in Western Kansas - Dhuyvetter, Kevin C.; Langemeier, Michael (My University, 2011)
This publication is a guide to budget estimate costs and returns for a season-long and an early-intensive grazing system in Western, KS.
MF1007_2011-01
Keywords: MF1007; Economics; Livestock; MF